2015 IEEE 27th International Conference on Tools With Artificial Intelligence (ICTAI) 2015
DOI: 10.1109/ictai.2015.53
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Extended Hierarchical Dependence Network Method Based on Non-hierarchical Predictive Classes and Applications to Ageing-Related Data

Abstract: We propose a novel algorithm for hierarchical classification, the Hierarchical Dependence Network based on non-Hierarchical Predictive Classes (HDN-nHPC) algorithm. HDN-nHPC uses relationships among predictive classes that are not descendants or ancestors of each other to improve classification performance and, at the same time, provide insights to non-obvious predictive class relationships. To test our algorithm and baselines, we have used hierarchical ageingrelated datasets where the classes are terms in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…This work uses the HDN-NSR variation of the HDN algorithm 100 (Fabris and Freitas, 2015), which uses a more sophisticated procedure to find the relationships between the classes of the hierarchy. It has been shown that HDN-NSR has overall better predictive performance than HDN and greater potential for finding relations that were not initially present in the class hierarchy, possibly useful for 105 biologists studying the ageing process.…”
mentioning
confidence: 99%
“…This work uses the HDN-NSR variation of the HDN algorithm 100 (Fabris and Freitas, 2015), which uses a more sophisticated procedure to find the relationships between the classes of the hierarchy. It has been shown that HDN-NSR has overall better predictive performance than HDN and greater potential for finding relations that were not initially present in the class hierarchy, possibly useful for 105 biologists studying the ageing process.…”
mentioning
confidence: 99%